2017
DOI: 10.1002/jmri.25665
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of accelerated simultaneous multislice diffusion‐weighted MRI of the prostate

Abstract: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1507-1515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…These studies hypothesized that the elevated noise floor in SMS-DWI may result in generally lower ADC values (21). However, several subsequent studies reported no significant differences in ADC values between SMS-accelerated sequences and C-DWI in several organs (15,16,26), which is in line with our results. Given that the ADC values of rectal cancer may reflect cancer aggressiveness by predicting the histologic T stage and differentiation (4,27,28) and that quantitative ADC measurement is useful in evaluating therapeutic response in rectal cancer after chemoradiotherapy (6)(7)(8), the comparable ADC values obtained with C-DWI and SMS-DWI in our study might be a prerequisite for reliable measurements and interpretation of ADC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These studies hypothesized that the elevated noise floor in SMS-DWI may result in generally lower ADC values (21). However, several subsequent studies reported no significant differences in ADC values between SMS-accelerated sequences and C-DWI in several organs (15,16,26), which is in line with our results. Given that the ADC values of rectal cancer may reflect cancer aggressiveness by predicting the histologic T stage and differentiation (4,27,28) and that quantitative ADC measurement is useful in evaluating therapeutic response in rectal cancer after chemoradiotherapy (6)(7)(8), the comparable ADC values obtained with C-DWI and SMS-DWI in our study might be a prerequisite for reliable measurements and interpretation of ADC.…”
Section: Discussionsupporting
confidence: 92%
“…The lesion conspicuity for rectal cancer was worse in SMS3-DWI than in kjronline.org SMS2-DWI and C-DWI, which may indicate worse diagnostic ability of SMS3-DWI. These findings correspond with the results of previous studies in other organs (15,16,21). The poor image quality in SMS-DWI with a high acceleration factor can be explained by the increasing geometry factor, which is related to image heterogeneity and signal-tonoise ratio (SNR) reduction (22,23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is possibly because our study did not include cystic lesions and fibrocystic changes. Moreover, our results showed that no significant deviations of ADC values were observed between SMS rs-EPI and conventional rs-EPI in the breast, which is consistent with several recently published studies [ 25 , 26 , 28 , 38 , 39 ]. The use of SMS technology in our research has no effect on ADC measurement.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying technique is based on the excitation of multiple slices simultaneously and the subsequent antialiasing to reconstruct the magnitude images. Simultaneous multislice sequences have successfully been tested for DWI of the human brain, 18 the breast, 19 the prostate, 20 the liver, the pancreas, 21 and the kidneys. 22 However, the SMS technique shows some limitations regarding image quality and signal-to-noise ratio due to aliasing problems between the simultaneous excited neighboring slices, which may affect diffusion measurements and IVIM analysis.…”
mentioning
confidence: 99%